Epidemiological Review: Mapping Cases and Prevalence of Helminthiasis in Indonesia on 2020-2022 - Trasia, Reqgi First (Jurnal Medis Islam Internasional, 2023)
Background: Helminthiasis cannot be separated from society in Indonesia. In 2020, the World Health Organization (WHO) classified helminth infections as neglected tropical diseases (NTD) that require large-scale control, because more than 23% of the world's population is infected with helminthiasis. In Indonesia, there are still few articles that comprehensively review the epidemiological mapping of the latest helminthiasis cases. The purpose of writing this article is to map the prevalence of helminthiasis in Indonesia in 2020-2022. This article is a systematic study  conducted from January-April 2023. The literature search was carried out through an electronic database. Result: The  findings of this study indicate that in the last three years, helminthiasis has not been eliminated in Indonesia. The  results of helminth species found to infest communities in several provinces in Indonesia include Ascaris lumbricoides, Trichuris trichiura, Hookworm, Hymenolepis nana, Taenia saginata, Taenia solium, Oxyuris vermicularis, Schistosoma japonicum, Strongiloides stercoralis, and Wuchereria bancrofti. The diagnosis of helminth infestation and infection is confirmed through microscopic examination by finding eggs, larvae, proglottids, and even adult worms that come out spontaneously through defecation. In addition, helminth transmission can occur through food contaminated with worm eggs. The government has tried to control helminthiasis through Permenkes number 15 of 2017 concerning Helminthiasis Management. However, the indicators of achieving the target of reducing the prevalence of intestinal worms to below 10% in each Regency/City as stated in Pasal 3 ayat 2 of the Permenkes have not been fully met. Conclusion: It can be seen in this study that there are still many provinces that have not reached the helminth control target. This condition is especially experienced by high-risk groups, such as children, mining workers, plantation workers, farmers, livestock workers, staff at slaughterhouses, and waste collectors.